THE ROLE OF ENVIRONMENTAL FACTORS IN SUPPORTING THE SPREAD OF LEPROSY IN DR SOETOMO HOSPITAL - Putri, Dyfe Alisya; Widia, Yuri; Alinda, Medhi Denisa; Romadhon, Pradana Zaky (International Journal of Health Science & Medical Research, 2026)
Leprosy is a chronic infectious disease caused by Mycobacterium leprae, primarily transmitted through respiratory droplets during prolonged and close contact with untreated individuals. Although it has a relatively low transmission rate, unfavorable environmental conditions can significantly increase the risk of disease spread. This study aims to identify and analyze the environmental factors that contribute to leprosy transmission. A descriptive quantitative study with a cross-sectional observational design was conducted. The study involved 222 leprosy patients with type 1 (reversal) reactions who were registered at the Morbus Hansen Outpatient Clinic from January 2015 to September 2024. Data were collected using structured questionnaires, field observations, and secondary data from medical records. Data were analyzed using descriptive and inferential statistics, with the Mann–Whitney test used to examine the relationship between environmental factors and leprosy cases. The results show that high population density, poor sanitation, inadequate household ventilation, limited access to clean water, and low socioeconomic status are factors significantly correlated with the high incidence of leprosy in the area. These findings highlight the importance of improving environmental conditions, alongside community education and enhanced access to healthcare services, as key components in the prevention and control of leprosy. Therefore, environment-based interventions should be integrated into a comprehensive strategy to eliminate leprosy in Indonesia.